Anthropomorphism in the Tafsir by the Ministry of Religious Affairs - Masri Mansoer (IJISH (International Journal of Islamic Studies and Humanities), 2022)
This study examines the tendency in schools of theology of the Tafsir by the Ministry of Religious Affairs of the Republic of Indonesia, especially in anthropomorphism, khalq al-Qur`an and ru`yatullah. This study is a library research, and the primary data is the Tafsir by the Ministry of Religious Affairs of  the Republic of  Indonesia that was published in 1996. Meanwhile, the secondary data is the works of the rational school of theology (Mu’tazila and Māturīdī Samarkand) and the traditional school of theology (Ashʿarī and Māturīdī Bukhara). After studying the sources above, it was found a number of verses of the Qur’an were used as naqli views by rational and traditional scholars, and then they explained their interpretation according to this Tafsir. Furthermore, a comparative interpretation analysis is carried out by applying the interpretation of the rational and traditional schools of theology to draw a conclusion about the school of theology in this Tafsir. The finding shows that the interpretation of anthropomorphic verses in this Tafsir is in line with Ashʿarīyah and Māturīdīyah Samarkand Beliefs. Hence, the Al-Qur’an is qadim (ancient or old), and God can be seen with the eyes of the believer in the hereafter.